HUBUNGAN KOINFEKSI TUBERKULOSIS DAN HUMAN IMMUNODEFICIENCY VIRUS (HIV) SERTA KAITANNYA DENGAN MULTI DRUG RESISTANT TUBERCULOSIS (MDR-TB) DI KOTA MEDAN TAHUN 2019 - ANNISA FITRI HENDEWI; HUMAIRAH MEDINA LIZA LUBIS (LP2MTBM MAKARIOZ, 2021)
Tuberculosis the infectious disease found most commonly in Human Immunodeficiency Virus (HIV) infection. Increase of coinfectionTB-HIV is the main cause of Drug Resistance TB in Indonesia. High mortality of TB-HIB in the world and Indonesiawith Increase MDR-TB case. This study used descriptive analytical method with retrospective design. Data processed useFisher Exact Test. The result showed that the relationship of TB-HIV with MDR-TB at Medan in 2019 show p value of 0.026(p<0.05). There is a significant relationship between the co-infection TB-HIV with MDR-TB at Medan in 2019.